Förderpreis Junge Künstler 1988. - Fiedler-Bender, Gisela; Költzsch, Georg-W.; Munkes, Hermann J.; Schmitt, Werner; Pfalzgalerie, Kaiserslautern (Saarbrücken : Saar Ferngas Aktiengesellschaft, 1988)
Thiel, Heiner ; Petry, Norbert ; Zimmerman, Ulrike ; Adrian, Martin ; Alt-Schäfer, Martina ; Bernasko, Martina ; Bischoff, Nicole ; Bosslet, Eberhard ; Dietz, Madeleine ; Eicher, Margret ; Erbach, Alexander ; Erzgräber, Bettina Sophie ; Fox, Johannes ; Frisch, Jochen ; Fuchs, Gerhard ; Glöckler, Manfred ; Grossmann, Frank-Joachim ; Holzkamp, Philipp ; Huber, Barbara ; Hübsch, Horst ; Kayser, Karl ; Klomann, Dirk ; Koblischeck, Bernd ; Kranz, Patricia ; Kreiensiek, Joachimm ; Lehnert, Volker ; Liebscher, Armin ; Mancke, Christoph ; Martin, Franz ; Mohr, Michael ; Oswald, Karlheinz ; Persel, Helga ; Plath, Georg ; Rousin, Karol ; Schäfer, Bernd ; Scheiblich, Volker ; Schewior, Sigrid ; Schmenger, Thomas ; Schmidt, Marcus ; Schreiber, Ulrich ; Stahlschmidt, Carmen ; Steiner, Helmut Philipp ; Steitz-Kramer, Christine ; Stephan, Michael ; van Haaren, Bettina ; Weiler, Erich ; Wiedemann, J.N.R. ; Wolf, Günter ; Zobel, Annette ; Zwick, Klaus
biografie
Förderpreis Junge Künstler 1988, Pfalzgalerie Kaiserslautern, 13. April bis 15. Mai 1988
Duits
boek